let K be Field; :: thesis: for M1, M2, M3, M4 being Matrix of K st len M1 = len M2 & len M2 = len M3 & len M3 = len M4 & width M1 = width M2 & width M2 = width M3 & width M3 = width M4 & M1 - M2 = M3 - M4 holds
M1 - M3 = M2 - M4

let M1, M2, M3, M4 be Matrix of K; :: thesis: ( len M1 = len M2 & len M2 = len M3 & len M3 = len M4 & width M1 = width M2 & width M2 = width M3 & width M3 = width M4 & M1 - M2 = M3 - M4 implies M1 - M3 = M2 - M4 )
assume that
A1: len M1 = len M2 and
A2: len M2 = len M3 and
A3: len M3 = len M4 and
A4: width M1 = width M2 and
A5: width M2 = width M3 and
A6: width M3 = width M4 and
A7: M1 - M2 = M3 - M4 ; :: thesis: M1 - M3 = M2 - M4
A8: ( len (- M4) = len M1 & width (- M4) = width M1 ) by ;
A9: ( len (M3 + (- M4)) = len M1 & width (M3 + (- M4)) = width M1 ) by ;
A10: ( len (- M2) = len M2 & width (- M2) = width M2 ) by MATRIX_3:def 2;
A11: ( len (M1 + (- M3)) = len M1 & width (M1 + (- M3)) = width M1 ) by MATRIX_3:def 3;
A12: ( len (M1 + (- M2)) = len M1 & width (M1 + (- M2)) = width M1 ) by MATRIX_3:def 3;
A13: ( len (M1 + (- M3)) = len M1 & width (M1 + (- M3)) = width M1 ) by MATRIX_3:def 3;
A14: ( len (M2 + (- M4)) = len M1 & width (M2 + (- M4)) = width M1 ) by ;
A15: ( len (- M3) = len M3 & width (- M3) = width M3 ) by MATRIX_3:def 2;
per cases ( len M1 > 0 or len M1 = 0 ) by NAT_1:3;
suppose len M1 > 0 ; :: thesis: M1 - M3 = M2 - M4
then M3 + (- M4) is Matrix of len M1, width M1,K by ;
then (M1 + (- M2)) + (- (M3 + (- M4))) = 0. (K,(len M1),(width M1)) by ;
then (M1 + (- M2)) + ((- M3) + (- (- M4))) = 0. (K,(len M1),(width M1)) by A1, A2, A4, A5, A8, Th12;
then (M1 + (- M2)) + ((- M3) + M4) = 0. (K,(len M1),(width M1)) by Th1;
then ((M1 + (- M2)) + (- M3)) + M4 = 0. (K,(len M1),(width M1)) by A1, A2, A4, A5, A15, A12, MATRIX_3:3;
then (M1 + ((- M2) + (- M3))) + M4 = 0. (K,(len M1),(width M1)) by ;
then (M1 + ((- M3) + (- M2))) + M4 = 0. (K,(len M1),(width M1)) by ;
then ((M1 + (- M3)) + (- M2)) + M4 = 0. (K,(len M1),(width M1)) by ;
then (M1 + (- M3)) + ((- M2) + M4) = 0. (K,(len M1),(width M1)) by ;
then (M1 + (- M3)) + ((- M2) + (- (- M4))) = 0. (K,(len M1),(width M1)) by Th1;
then (M1 + (- M3)) - (M2 + (- M4)) = 0. (K,(len M1),(width M1)) by A1, A4, A8, Th12;
hence M1 - M3 = M2 - M4 by ; :: thesis: verum
end;
suppose len M1 = 0 ; :: thesis: M1 - M3 = M2 - M4
then ( len (M1 - M3) = 0 & len (M2 - M4) = 0 ) by ;
hence M1 - M3 = M2 - M4 by CARD_2:64; :: thesis: verum
end;
end;